Engineered immunological niche directs therapeutic development in models of progressive multiple sclerosis - Laila M. Rad; Kevin R. Hughes; Sydney N. Wheeler; Joseph T. Decker; Sophia M. Orbach; Angelica Galvan; Jasmine Thornhill; Kate V. Griffin; Hamza Turkistani; Russell R. Urie; David N. Irani; Lonnie D. Shea; et al. (Proceedings of the National Academy of Sciences, 2025)
Primary progressive multiple sclerosis (MS) is a demyelinating autoimmune disease with only a single class of FDA-approved treatment, B cell depletion. Novel treatments could emerge from a deeper understanding of the interplay between multiple cell types within diseased tissue throughout progression. We initially describe an engineered biomaterial–based immunological niche (IN) as a surrogate for diseased tissue to investigate immune cell function and phenotype dynamics throughout a chronic progressive mouse model of MS. Using these niches, we identify an array of dysregulated CC chemokine signaling as potential targets. We then develop antigen-loaded nanoparticles that reduce CC chemokine signaling, while delivering antigen. These nanoparticles serve as an antigen-specific treatment, and a single injection reduces disease burden, even if administered after symptomatic disease onset. This report demonstrates proof of principle of a biomaterial scaffold as a diseased tissue surrogate that can monitor immune function, identify potential drug targets, and guide the development of a therapeutic.